(untitled) (Fiep Bulletin - online, 2014)
This article is born of memorials, ways discovered to long of the reflections the proposals in the formation of educators of Infancies. When working with the memories, we were producing histories, experiences, experiences and other forms of action in the daily one of the School. This movement of not linear formation allowed that generating subjects were unchaining new quarrels, following the routes of the reflection on infancies and the time of the school. We use a methodology that contemplated speaks of the educators, comments registered in the daily one of field, souvenirs of infancies, the tricks, the toys, the marks of the school. They are, therefore, stretches of written texts, comments carried through in the lessons and the readings of studious of these thematic ones. We were remembering to our things of child, opening the old trunks and joining multicolored remnants, with many forms, full of meanings in infancies. Moments of magic, creation, the time without time of the dreams, of the solitude ahead of the stranger, the haste them to grow fast, to be adult to make things not allowed. In the meeting we were breaching with the time of the clock and incorporating the listening of the signals of the time in beating of the cosmic heart. Walking for many spaces and times, we forget many things, we reviewed the marks in the bodies, remember the joys of the streets, the entrances and in the exits of the schools. We grow in we become, adults and we forget them pedlar’s wares kept in the trunks them infancies.